Trust is the common denominator for COVID-19 vaccine acceptance: A literature review - Bipin Adhikari; Phaik Yeong Cheah; Lorenz von Seidlein (Vaccine: X, 2022)
Vaccine hesitancy and refusal to be vaccinated are major reasons why mass vaccination strategies do not reach the intended coverage, even if adequate vaccine supply has been achieved. The main objective of this study is to explore the role and contribution of trust in public willingness to accept COVID-19 vaccinations. The study utilised a qualitative synthesis of literature around hesitancy, willingness to accept vaccination, and the role of trust. Data were extracted from the literature and first categorised using a deductive approach, and later analysed in QSR NVivo using a mix of deductive and inductive approaches. The impact of trust was mostly borne out in the willingness to accept a vaccine, but details on what trust is, how and why it affects willingness or lack of it, was not frequently reported. Three types of trust were identified: 1) Trust in the quality and safety of vaccines; 2) Institutional trust; and 3) Interpersonal trust in the professionals who communicate about and administer the vaccine. Trust in the vaccines’ quality and safety, and institutional affiliation significantly contributed towards willingness to be vaccinated. The bulk of the literature focused on how interpersonal trust and personal attributes of potential vaccinees affected the willingness to accept the vaccine. This complex relationship included a fragility of beliefs and perceptions at an individual level, with a bidirectional relationship to societal perceptions. Perceptions of vaccines had a predominant role in decision-making, in contrast to more science-based decision-making. Although globally, the perceptions and beliefs contributing to trust had commonalities and relevance, trust was often found to be dependent on factors embedded in local social, cultural, institutional, and individual attributes and experiences. Understanding different types of trust offers potential approaches to motivate undecided people to receive vaccine; and vaccine refusers to revisit their decisions.